Sasakawa, the warrior for peace, the global philanthropist - Daventry, Paula (Pergamon Press, 1987)
Ryoichi Sasakawa's avowed goal in life is the pursuit of world peace and the betterment of mankind. He is one of the world's greatest philanthropists - the biggest individual donor to the United Nations and the World Health Organization - and his humanitarian interests extend from refugee aid to leprosy relief. This second edition of Mr Sasakawa's biography traces his life from its humble origins to its present success and charts the continuing development of his worldwide philanthropic activity, including that for the victims of the famine in Africa.